Morale and Mass Observation: Governing the Affective Atmosphere on the Home-Front - Dibley, Ben; Kelly, Michelle (Museum and Society, 2015)
This paper focuses on Mass Observation (MO)’s morale work, commissioned by the British Government over the period 1939–41. It examines the ways in which MO’s earlier collecting practices were recomposed through its research into civilian morale, and linked up with national centres of calculation, in particular the Ministry of Information (MoI). We explore the associations through which civilian morale was established, simultaneously, as an autonomous object of knowledge and as a particular field of intervention. As an object of knowledge, morale posited the existence of a dynamic affective ‘atmosphere’ associated with collective everyday life, which could be calibrated through various social scientific methods. As a particular field of intervention, technicians of morale postulated that this atmosphere might be regulated through various policy instruments. This paper traces the ways in which MO practices were implicated along these two axes in the emergence of civilian morale as a domain warranting the state’s ‘constant attention and supervision’.